Familia și delincvența juvenilă - Fleșner, Margareta (Calitatea Vieții, 1994)
Family life deeply affects the delinquent teenagers. Their family lack of cohesion, the material difficulties it is confronted to, their parents misunderstandings, the affective rejection they are forced to cope with - these are only a few reasons for their deviance. These conditions lead to the conclusion that the family lacks (material, educational, affective, moral) draw the major causal coordinate of their delinquent behavior.